Cocatalyst‐Free Reduction of 4, 4′‐Dinitrodiphenyl Ether to 4, 4′‐Diaminodiphenyl Ether Over Twin‐Crystal ZnxCd1−xS under Visible Light. Issue 21 (31st August 2021) - Hu, Yujia; Yu, Guiyang; Xing, Chuanwang; Liu, Shanshan; Wei, Chuangyu; Liu, Heyuan; Jiang, Jianzhuang; Li, Xiyou
Abstract: Semiconductor‐based photocatalytic conversion of solar energy is a promising method for the synthesis of high value‐added chemicals. In this paper, a cocatalyst‐free nano‐twin crystal Znx Cd1−x S (T−Znx Cd1−x S) semiconductor was employed to achieve almost complete conversion of DNDPE and the yield of ODA product achieves >99 % in 40 min reaction time without additional hydrogen source. As far as we know, this is the first time to apply the photocatalytic technology for reducing DNDPE to ODA, and the photocatalytic efficiency has greatly exceeded the result of traditional catalytic method. Theoretical calculation and isotope labeling in situ HPLC‐MS analysis demonstrates that the reduction mechanism of DNDPE is two nitro groups of DNDPE are separately instead of simultaneously reduced, following the process of DNDPE→NO2 −C6 H4 −O−C6 H4 −NO→NO2 −C6 H4 −O−C6 H4 −NHOH→NO2 −C6 H4 −O−C6 H4 −NH2 →NO−C6 H4 −O−C6 H4 −NH2 →NH2 −C6 H4 −O−C6 H4 −NHOH→ODA. Hydrogen protons of water, instead of ethanol, provide the hydrogen source for the photocatalytic reduction of DNDPE to ODA. Abstract : Twin Crystal Catalysis : A highly‐efficient cocatalyst‐free nano‐twin crystal Znx Cd1−x S is employed to achieve highly efficient conversion of DNDPE with ∼99 % and the yield of ODA product with >99 % within 40 min reaction time under mild and environmentally friendly reaction condition.